Implementation of the Climate-Concerned Village Policy in Mekarmulya Village, Talegong District, Garut Regency - Husni Farhani M; M. Ridwan Caesar; Fadlan Abdillah; Iin Endah Setyawati; Cecep Sapardin (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study aims to analyze the implementation of the Climate Care Village Policy (Desa Peduli Iklim) in Mekarmulya Village, Talegong District, Garut Regency. This policy is part of a national program focusing on community-based climate change mitigation and adaptation. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and literature studies. The results show that the implementation of the policy has not been optimal due to limited human resources, lack of socialization, and weak village bureaucratic structure. Communication, resources, disposition, and bureaucratic structure are the main factors determining the success of the policy as stated by Edward III. Efforts to improve implementation can be carried out through strengthening village apparatus capacity, forming special working units, and increasing community participation. Keywords: Public Policy Implementation, Climate Care Village, Public Administration